Efektivitas Kebijakan Program Cinta Bangga dan Paham Rupiah di Kabupaten Nunukan - Mawar, Mawar; Rahman, Abdul; Evi Satispi (Universitas Medan Area, 2023)
This article aims to analyze the effectiveness of the love, pride and understanding of the rupiah program policy in Nunukan Regency. The problem focuses on the lack of public awareness of using the rupiah currency in the Indonesia-Malaysia border area (especially in Nunukan Regency). In order to approach this problem, 3 main policy/program parameters are used as a reference, namely: love, pride and understanding of the Rupiah as set by Bank of Indonesia. Data were acquired through the collection of both primary and secondary data sources. Primary data was procured via observations and questionnaires disseminated to 50 respondents, and it was subsequently assessed using a Likert scale. Conversely, secondary data was sourced from various policy documents. This article yields the conclusion that the evaluation of the